KEPRIBADIAN PEMIMPIN PEREMPUAN DALAM PERSPEKTIF ISLAM - Rodliyah, St (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2014)
Abstract: Woman is Godâs creature which beautiful, gentle, and always fascinate man. Hence al-Quran only saying that man tendency to woman, not on the other side. In that position, pushing woman tobe glamor in every opportunity. In this life, woman have various role,beside as wife, as mother to its child, as career woman at office, as leader in their society and others. To be success its duty, hence muslimah woman have to remain towards in the Islam norms, have good personality and also excellent behavior. Woman beauty represent God send of Allah of SWT which must thank to and take care of, as well as possible. The beauty of woman (muslimah) will be seen if subvention with good personality.ÙÙØ®Øµ: Ø§ÙÙØ³Ø§Ø¡ ÙØ®ÙÙÙØ§Øª Ø§ÙÙÙ ÙÙ ÙÙ Ø§ÙØ±Ø¬Ø§Ù Ø¬ÙÙÙ Ø ÙØ·ÙÙ Ø Ù Ø¯Ø§Ø¦ÙØ§ Ø±Ø§Ø¦Ø¹Ø©. ÙÙØ°ÙÙ ÙØ¥Ù Ø§ÙÙØ±Ø¢Ù ÙÙÙÙ ÙÙØ· Ø£Ù Ø§ÙØ±Ø¬Ø§Ù ØªØ²ÙÙ ÙÙØ³ÙØ§ Ø´ÙÙØ© Ø§ÙÙÙÙ Ø¥ÙÙ Ø§ÙÙØ³Ø§Ø¡ Ø ÙÙÙØ³ Ø§ÙØ¹ÙØ³ . Ø§ÙÙÙÙÙ ØØªÙ Ø Ø±Ø¨ÙØ§Ø Ø£Ù ØªØ´Ø¬ÙØ¹ Ø§ÙÙØ³Ø§Ø¡ Ø¹ÙÙ Ø§ÙÙÙÙ Ø¥ÙÙ Ø§ÙØ¸ÙÙØ± Ø§ÙÙØ§ÙÙ ÙÙØ³ØØ± ÙÙ Ø£Ù ÙÙØ§Ø³Ø¨Ø©. ÙÙ Ø§ÙØÙØ§Ø©Ø Ù Ø§ÙÙØ±Ø£Ø© ÙØ¯ÙÙØ§ ÙØ¬ÙÙØ¹Ø© ÙØªÙÙØ¹Ø© ÙÙ Ø§ÙØ£Ø¯ÙØ§Ø± ÙØ«Ù Ø§ÙØ²ÙØ¬Ø© Ø Ù Ø§ÙØ£Ù ÙØ·ÙÙÙØ§ Ø ÙØ§ÙØ±Ø£Ø© Ø§ÙÙÙÙÙØ© ÙÙ ÙÙØ§Ù Ø§ÙØ¹ÙÙØ ÙØ´Ø±ÙØ© Ø±Ø§Ø¦Ø¯Ø© ÙÙ Ø§ÙÙØ¬ØªÙØ¹ ÙÙÙØ°Ø§ Ø¯ÙØ§ÙÙÙ. ÙÙÙÙÙ ÙØ§Ø¬ØØ§ ÙÙ Ø§ÙÙÙØ§Ù Ø¨ÙØ§Ø¬Ø¨Ø§ØªÙÙ Ø Ø«Ù Ø§ÙÙØ³Ø§Ø¡ Ø§ÙÙØ³ÙÙØ§Øª ÙØ¬Ø¨ Ø£Ù ÙØ§ ØªØ²Ø§Ù ØªÙØªØ²Ù ÙÙØ§Ø¹Ø¯ Ø¯ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù Ø ÙÙØ¯ÙÙ Ø´Ø®ØµÙØ© Ø¬ÙØ¯Ø© Ù Ø§ÙØ·Ø§Ø¨Ø¹ Ø§ÙÙØ¨ÙÙ. Ù ÙÙØ¯ ÙÙ Ø§ÙØ±Ø£Ø© Ø§ÙØ¬ÙØ§Ù ÙÙ ÙØ¨Ø© ÙÙ Ø§ÙÙÙ ÙÙØ°Ø§ ÙÙØ¨ØºÙ Ø§ÙØ§ØØªÙØ§Ù Ù Ø§ÙØÙØ§Ø¸ Ø¹ÙÙÙØ§ ÙÙØ°ÙÙ ÙÙÙÙ . Ù Ø¹ÙÙ ÙØÙ ÙØªØ²Ø§ÙØ¯ Ø£Ù ÙÙØ¸Ø± Ø¥ÙÙ Ø¬ÙØ§Ù Ø§ÙÙØ±Ø£Ø© ( Ø§ÙÙØ³ÙÙØ© ) Ø¹ÙÙ ØØ§ÙÙØ§ Ø¥Ø°Ø§ Ø¯Ø¹ÙØª ÙØ¹ Ø´Ø®ØµÙØ© Ø³Ø§ØØ±Ø©.Keyword: Kepribadian, pemimpin perempuan, perspektif Islam